Resource Use Efficiency for Cowpea Production in Akatsi District of Ghana - F, Nimoh; S, Asuming-Brempong (Asian Journal of Agriculture and Rural Development, 2012)
Cowpeas have been identified as one of the crops with the highest and cheapest source of protein which can be relied on to help curb malnutrition problem in most developing countries. Farmers in most farming communities in Ghana, such as Akatsi in the Volta region, still practice the ‘tradition bound’ agriculture. The returns from such production system are estimated to be below potential levels. Assessment of the productivity of major inputs employed in the production of cowpeas in the study area indicates that outputs are below maximum potentials. The level of inputs such as farm size, labour, pesticide, and ploughing (land preparation) were found to be positively related to output, while quantity of seed was negatively related to output. The marginal value products (MVPs) of the inputs were lower than their unit costs. It is anticipated that farmers could increase production beyond current levels, if the resources employed are utilized efficiently. Among the problems identified to affecting the production of cowpeas in the study area include: unfavorable climate, incidence of pests and diseases, land tenure problem, lack of credit for operation, lack of storage facility, transportation and lack of ready market for the produce. To help improve the production, and hence farmers’ income and their living standards, there is the need for an accelerated education programme to provide information on the appropriate methods of production, especially on how inputs could be allocated by the resource-poor farmers.